Isaac in the Old Testament : a new interpretation from Genesis 22, based on hermeneutical-methodological and exegetical investigations - Le Roux, J.H. (Jurie Hendrik), 1944- (University of Pretoria, 2013)
Thesis (DD)--University of Pretoria, 2009.